Effects of Sodium Alginate on the Flotation Separation of Molybdenite From Chalcopyrite Using Kerosene as Collector - Zeng, Guangsheng; Ou, Leming; Zhang, Wencai; Zhu, Yuteng (Frontiers in Chemistry, 2020)
In this paper, the effect of sodium alginate (SA) on the flotation separation of molybdenite from chalcopyrite using kerosene as collector was systematically investigated. The results of single-mineral micro-flotation tests indicated that SA exhibited strong depression on chalcopyrite flotation while imposed no impact on the floatability of molybdenite. However, in the chalcopyrite-molybdenite mixed-mineral flotation system, the presence of chalcopyrite significantly increased the depressing effect of SA on molybdenite flotation, leading to a considerable reduction in the flotation selectivity. The negative impact of chalcopyrite on the performance of SA in molybdenite flotation was eliminated by adding a certain dosage of kerosene prior to SA. A concentrate containing 53.43% of Mo was obtained at 76.90% of recovery using 19 mg/L kerosene and 40 mg/L SA at pH 5.4. Zeta potential measurements indicated that the adsorption of SA on chalcopyrite surfaces was stronger than that on molybdenite surfaces, which agreed with the single-mineral flotation test results. The adsorption of SA on chalcopyrite was further confirmed to be chemisorption by FTIR spectra analyses. When Cu2+ appeared in solution, the flotation of molybdenite was strongly depressed by SA. Mechanism analyses indicated that more active sites were generated on molybdenite surfaces after the addition of Cu2+ thus promoting the adsorption of SA.